Desenvolvimento e qualidade da água de fruto de cultivares de coqueiro anão - Silva, Geomar Galdino da (2006)
The coconut tree is an originary plant of southeastern Asian. Although the cultivation of this fruitbowl occurs predominantly in the Northeast region, currently, new regions of the country are exploring this culture. Coconut tree is the bigger economic expression in the income generation, feeding and a products variety. In relation to the fruit, few studies had been carried out relating development, harvest point and the water quality. Given the importance of the coconut cultivation and the expansion of the new areas planting with dwarf coconut tree, the aimed of this research was to evaluate the development of fruits of different dwarf cultivars aiming to get subsidies for the determination of more adjusted indices of harvest for the market to in natura and/or industrialized coconut water. To this, three experiments with Green Dwarf of Jiqui, Yellow of Malaysia, Yellow of Gramame, Red of Gramame, Red of Cameroon and Malaysia Red cultivars cultivated in an experimental area located at Unidade de Execução de Pesquisa da Embrapa Meio-Norte, in Parnaíba, Piauí state. In the first phase of the research, plants were selected at random and inflorescences that presented fertile flowers were marked, that is, fifteen days after the opening of the espata. After that, harvests since marking until the 210 days age were made. The analyses were carried out at Laboratório de Fisiologia e Tecnologia Pós-colheita da Embrapa Agroindústria Tropical, in Fortaleza, Ceará state. Was used a completely randomized design in 6 x 10 factorial scheme with three composed replications with five fruits for plot. During the development, the fruits were evaluated about fresh and dry mass, color, diameter and length (fruit and internal cavity), solid endosperm thickness, volume and water mass. In the second and third phases of the research the water was evaluated in relation to soluble solids content (TSS), total soluble sugars (TSA), reducing sugar (AIR), trititable acidity (AT), pH, SST/AT ratio, turbidez, sensorial and mineral analysis. The period understood between 120 and 180 days, corresponded the biggest growth taxes of the fruit, increase in the fresh mass and final volume of water in almost all cultivars. The harvest of the fruits for the in natura and/or industrialized water consumption can be made between 180 and 210 days, after anteses, when the same ones reach the maximum growth with better quality of waters. The water of cultivars presented expressive calcium, sodium and phosphorus amounts, being potassium the mineral element more exported by the coconut fruit.